2022
DOI: 10.1111/apt.17179
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta‐analysis: efficacy of peppermint oil in irritable bowel syndrome

Abstract: Summary Background Irritable bowel syndrome (IBS) is one of the most common disorders of gut‐brain interaction, with a complex pathophysiology. Antispasmodics are prescribed as first‐line therapy because of their action on gut dysmotility. In this regard, peppermint oil also has antispasmodic properties. Aim To update our previous meta‐analysis to assess efficacy and safety of peppermint oil, particularly as recent studies have cast doubt on its role in the treatment of IBS Methods We searched the medical lite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…The effects of peppermint EO have been attributed to its antimicrobial and antispasmodic activity [ 32 ]. A recent systematic review and meta-analysis on the efficacy of peppermint EO in improving IBS analyzed, overall, 10 placebo-controlled randomized trials with minimum duration of four weeks, involving a total of 1030 patients [ 37 ]. Both small-intestine-release microencapsulated oil (182–540 mg/day) and regular peppermint oils (2 mL/day) were investigated in the different trials.…”
Section: Essential Oils Helpful In the Irritable Bowel Syndrome (Ibs)mentioning
confidence: 99%
See 2 more Smart Citations
“…The effects of peppermint EO have been attributed to its antimicrobial and antispasmodic activity [ 32 ]. A recent systematic review and meta-analysis on the efficacy of peppermint EO in improving IBS analyzed, overall, 10 placebo-controlled randomized trials with minimum duration of four weeks, involving a total of 1030 patients [ 37 ]. Both small-intestine-release microencapsulated oil (182–540 mg/day) and regular peppermint oils (2 mL/day) were investigated in the different trials.…”
Section: Essential Oils Helpful In the Irritable Bowel Syndrome (Ibs)mentioning
confidence: 99%
“…Both small-intestine-release microencapsulated oil (182–540 mg/day) and regular peppermint oils (2 mL/day) were investigated in the different trials. The analysis demonstrated that peppermint EO was more effective than placebo in all 10 trials in terms of either global symptoms or abdominal pain, concluding that peppermint is an efficacious treatment for IBS [ 37 ].…”
Section: Essential Oils Helpful In the Irritable Bowel Syndrome (Ibs)mentioning
confidence: 99%
See 1 more Smart Citation
“…We read the study by Ingrosso et al 1 with interest. A previous network meta-analysis showed that peppermint oil, as an antispasmodic drug, is efficient in attenuating global IBS symptoms.…”
Section: Letter: Efficacy Of Peppermint Oil In Irritable Bowel Syndromementioning
confidence: 99%
“…Herbal remedies exert a broad spectrum of pharmacological actions (multi-target approach) combined with proven good tolerability [ 8 ] . Some herbal compounds exert prokinetic or anti-infl ammatory actions; volatile essential oils like peppermint oil [ 9 ] or caraway oil have strong carminative eff ects due to defoaming and spasmolytic activities [ 10 ] . Other herbal compounds seem to in-fl uence the microbiome by antibacterial and antifungal eff ects.…”
Section: Introductionmentioning
confidence: 99%